The Mediating Role of Training Behaviors on Self- Reported Mental Toughness and Mentally Tough Behavior in Swimming - Beattie, S.; Alqallaf, A.; Hardy, L.; Ntoumanis, Nikos (American Psychological Association, 2018)
Self-regulated training behaviors play a vital role in athletes' physical and mental sporting development. The purpose of the present study was to investigate the mediating role of self-regulated training behaviors (self- and coach-rated) on the relationship between self-reported mental toughness (MT) and coaches' perceptions of swimmers' mentally tough behavior (MTb) in competition. A second purpose of the study was to examine how discrepancies in coach and athlete perceptions of training behaviors related to coach perceptions of swimmers' MTb in competition. A sample of 12 swimming coaches (11 men and 1 women) and 208 of their competitive swimmers (86 men and 122 women) participated in the study. The swimmers completed self-report assessments of MT and self-regulated training behaviors. The coaches completed questionnaires regarding observations of their swimmers' MTb in competition and a smaller pool of items from the athletes self-regulated training behaviors questionnaire. Findings supported our hypotheses that MT was positively related to self-regulated training behaviors (self- and coach-rated), and training behaviors were positively related to coach-rated MTb. Further, self-regulated training behaviors (ß = 0.12; confidence interval [CI; 0.05, 0.20]) and coach-rated perceptions of training behaviors (ß = 0.07; CI [0.03, 0.13]) mediated the relationship between self-report MT and coach-rated MTb in competition. Finally, a significant amount of variance in MTb was accounted for (23%) only when there was agreement between the coach and the athlete regarding the level of self-regulated training behaviors. We recommend that future research examines what specific types of training behaviors positively influence MT.